Paper from cotton waste - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A paper industry in a Sahelian country menaced by drought and desertification seems inconceivable but Mali has a 'paper workshop' where engineers are experimenting with paper-making from alternative raw materials including cotton stalks. Cotton is...